Determination of single-nucleotide polymorphism in the proximal promoter region of apolipoprotein M gene in coronary artery diseases - Zheng, Lu (Dove Medical Press, 2009)
OBJECTIVE: It has been reported that single-nucleotide polymorphism (SNP) in the proximal promoter region of apolipoprotein M (apoM) gene may confer the risk in the development of type 2 diabetes (T2D) and coronary artery disease (CAD) in the Han Chinese. However, in a recent study demonstrated that plasma apoM level did not correlated to the coronary heart disease. In the present studies, we investigated the SNP T-778C of apoM gene in CAD patients and controls in the Han Chinese population. Moreover we examined whether serum apoM levels could be influenced by this promoter mutation. MATERIAL AND METHODS: One hundred twenty-six CAD patients and 118 non-CAD patients were subjected in the present study. All patients were confirmed by the angiography. The genotyping of polymorphisms T-778C in apoM promoter was determined by real-time polymerase chain reaction. Serum apoM levels were semi-quantitatively determined by the dot-blotting analysis. RESULTS: Distribution of apoM T-778C genotype in non-CAD patients was as following: 84.7% were T/T, 15.3% were T/C and 0.0% was C/C. T allele frequencies were 92.4% and C allele, 7.6%. In the CAD patients, 99 patients (78.6%) had the T/T genotype, 25 patients (19.8%) with T/C genotype and 2 patients (1.6%) with C/C genotype. The allele frequency was 88.5% for the T allele and 11.5% for the C allele. There was no statistical significant difference of serum apoM levels found in these three genotypes. CONCLUSIONS: There was no significant difference in allele or genotype frequencies between CAD patients and non-CAD patients. Binary logistic regression analysis with adjustments for age, gender, triglycerides, total cholesterol, low-density lipoprotein, high-density lipoprotein, apoAI, apoB, and LP(a) indicated that the TC and CC genotypes in SNP T-778C were not significantly associated with the development of CAD (odds ratio = 1.510, 95% confidence interval: 0.756–3.017; p = 0.243).